Finding the North Pole : Dr. Cook's own story of his discovery, April 21, 1908 : the story of Commander Peary's discovery, April 6, 1909 : together with the marvelous record of former Arctic expeditions - Morris, Charles, 1833-1922. ([Philadelphia? : s.n.], 1909)
The dramatic announcements of Cook and Peary -- Cook's story of his discovery of the North Pole -- The story of Peary's great exploit -- Side-lights on the Peary expedition -- Early life and experiences of Dr. Frederick A. Cook -- Cook in the Antarctic and in Alaska -- Bradley's account of the Cook expedition -- Robert E. Peary, the indomitable Polar explorer -- Peary crosses Greenland -- Peary's farthest North of 1905-6 -- Europe gives honor to Dr. Cook -- Receptions of Cook and Peary on American soil -- The controversy between Cook and Peary -- Interesting scientific work in the Arctic -- Animals of the Arctic region -- Terrors and mysteries of the Polar regions -- The search for the Northwest Passage -- The Ross and Parry Polar voyages -- The first Franklin expeditions -- The terrible fate of the Sir John Franklin expedition -- Dr. Kane's famous Arctic voyage -- Hayes, Hall and other hardy adventurers -- Nordenskiold and the Northeast Passage -- The horrors of the "Jeannette" expedition -- Melville finds the remains of the DeLong party -- Greely's Arctic winter of starvation -- Nansen's memorable voyage in the "Fram" -- Andree's fatal flight northward in a balloon -- Modern Vikings in the Arctic seas -- Abruzzi, the royal Italian explorer -- The problem of the Antarctic zone -- Shackleton on the threshold of the South Pole. Mode of access: Internet.